Clinical Hypnosis in Pediatric Crohn's Disease: A Randomized Controlled Pilot Study. Issue 3 (3rd March 2021) - Lee, Amanda; Moulton, Dedrick; Mckernan, Lindsey; Russell, Alexandra; Slaughter, James C.; Acra, Sari; Walker, Lynn
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Objective: The aim of this study was to implement clinical hypnosis (CH) as an adjunctive therapy for adolescents with Crohn's disease (CD) and to assess the impact of CH on quality of life (QoL), abdominal pain, psychosocial measures, and disease activity compared with standard care. Methods: Forty adolescents with CD were randomized to a hypnosis intervention (HI) or waitlist control (WC) group. The intervention consisted of 1 in-person CH session, self-hypnosis education, and recordings for home practice. Data was collected at baseline, after the 8-week intervention, and at week 16. The primary outcome was patient- and parent-reported QoL; secondary outcomes were patient-reported abdominal pain, depression, anxiety, and sleep; school absences; and disease activity by Pediatric Crohn's Disease Activity Index. Paired and independent t -tests were used to compare differences from baseline to postintervention within and between groups. Results: Forty patients (50% girls, mean 15.8 years) were enrolled from February to May 2019. Seventy-eight percent had inactive disease, and 55% had abdominal pain. Post intervention, significant improvements were noted in HI parent-reported QoL compared with WC in total score ( P = 0.05), social functioning ( P = 0.01), and school functioning ( P = 0.04) but patient-reported QoL was unchanged. Abdominal pain severity significantly improved in HI compared with WC ( P = 0.03). School absences decreased in significantly more intervention than control patients ( P = 0.01). Patients who practiced self-hypnosis consistently showed a trend toward greater QoL improvement than those who did not ( P = 0.1). Conclusions: CH is an acceptable and feasible adjunct in CD and may improve psychosocial QoL and abdominal pain. Further research is warranted.